2017
DOI: 10.3136/fstr.23.481
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory Validation Study of a Singlet Oxygen Absorption Capacity Assay Method for Determining the Antioxidant Capacities of Antioxidant Solutions and Food Extracts

Abstract: Singlet oxygen absorption capacity (SOAC) is an assay method used to evaluate the singlet oxygen quenching capacity. We evaluated the precision of the SOAC assay method in an inter-laboratory validation study using 3 antioxidant solutions and 3 food extracts. This study involved 14 participating laboratories, with data sets from 8 successfully participating laboratories subjected to statistical analysis. In accordance with the harmonized protocol, this study showed that the intermediate precision relative stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, a modified method using a microplate reader has been established, enabling SOAC to be applied as a high throughput assay (Takahashi et al, 2016). This modified SOAC method has been validated in an inter-laboratory test (Wakagi et al, 2017). Previous studies have reported ORAC values of various foods as their antioxidant capacity; however, the values provide only the radical scavenging activity within the total antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a modified method using a microplate reader has been established, enabling SOAC to be applied as a high throughput assay (Takahashi et al, 2016). This modified SOAC method has been validated in an inter-laboratory test (Wakagi et al, 2017). Previous studies have reported ORAC values of various foods as their antioxidant capacity; however, the values provide only the radical scavenging activity within the total antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The precision of the SOAC assay method was evaluated in an inter-laboratory validation study (41). SOAC values were measured for 3 AO solutions (i.e.…”
Section: Validation Studymentioning
confidence: 99%
“…The SOAC values measured using a microplate reader were in good agreement with the corresponding those measured using an UV-vis spectrophotometer. The SOAC assay method was validated by inter-laboratory validation study due to 14 laboratories (41).…”
Section: Carotenoidmentioning
confidence: 99%